Footcare knowledge and practice among diabetic patients attending primary health care centers in Jazan region, Saudi Arabia - Gasem Darraj; Mohammed Somaili; Samy Shaban; Mohammed Jahlan; Abdulaziz Darraj; Banan Ahmed; Gasem Mojamamy; Mohammed Darraj; Hesham Dahlan; Ahmad Alqassim (Journal of General and Family Medicine)
Abstract Background Diabetic foot is one of the significant complications of diabetes mellitus, associated with a high risk of morbidity and mortality. Patients' knowledge of, and willingness to practice, good footcare are essential and may decrease these risks. This study was conducted to assess adult diabetic patients' knowledge of footcare and willingness to put their knowledge into practice. Method A cross‐sectional observational study was conducted on adult diabetic patients in the central area of the Jazan Region using patients' responses to a questionnaire. Descriptive statistics were calculated for study variables, and the Pearson chi‐squared test was used to compare categorical data. Results A total of 410 diabetic patients were included in this study. The mean age of the participants was 56.7 years. The mean duration of their diabetes mellitus (DM) to date was 9.2 years, and 63% had complications of diabetes. For the questionnaire, 56% of the patients gave incorrect responses to the knowledge of the footcare section and 81% to the willingness to practice footcare section. Highly educated patients have better knowledge and practice of diabetic footcare than those who are less educated (77% vs. 23%, p < 0.05), (37% vs. 20%, p < 0.05), respectively. A statistically significant difference exists between patients with good and poor knowledge scores. Conclusion This study demonstrates that the knowledge and practice of footcare among DM patients are poor. Therefore, appropriate patient information programs are needed to increase patients' understanding of their illness and how to manage it.